Multiphysics analysis of the dual role of magnetoelectric nanoparticles in a microvascular environment: from magnetic targeting to electrical activation - Lenzuni, Martina; Giannoni, Paolo; Chiaramello, Emma; Fiocchi, Serena; Suarato, Giulia; Ravazzani, Paolo; Marrella, Alessandra (Frontiers in Bioengineering and Biotechnology, 2025)
Minimally invasive medical treatments for peripheral nerve stimulation are critically needed to minimize surgical risks, enhance the precision of therapeutic interventions, and reduce patient recovery time. Magnetoelectric nanoparticles (MENPs), known for their unique ability to respond to both magnetic and electric fields, offer promising potential for precision medicine due to their dual tunable functionality. In this study a multi-physics modeling of the MENPs was performed, assessing their capability to be targeted through external magnetic fields and become electrically activated. In particular, by integrating electromagnetic, fluid dynamics, and biological models, the efficacy of MENPs as wireless nano-tools to trigger electrical stimulation in the peripheral Nervous system present within the dermal microenvironment was assessed. The simulations replicate the blood venous capillary network, accounting for the complex interactions between MENPs, blood flow, and vessel walls. Results demonstrate the precise steering of MENPs (>95%) toward target sites under a low-intensity external magnetic field (78 mT) even with a low susceptibility value (0.45). Furthermore, the extravasation and electrical activation of MENPs within the dermal tissue are analyzed, revealing the generation of high-induced electric fields in the surrounding area when MENPs are subjected to external magnetic fields. Overall, these findings predict that MENPs can be targeted in a tissue site when intravenously administrated, dragged through the microvessels of the venous system, and activated by generating high electric fields for the stimulation of the peripheral nervous system.